Penyuluhan Pentingnya Menjaga PHBS sebagai Upaya Preventif Penyebaran Infeksi Hepatitis A di TPA Masjid Al-Ikhlas, Surakarta - Gading Nasywaa Aji Azzahra (Journal of Midwifery in Community (JMC), 2023)
Background: Cases of hepatitis A, which often infect children, are increasing day by day. Based on WHO data, 1,017,290 people have been infected with hepatitis A, the majority of whom are in the age group of 5-14 years. However, the problem is getting worse with the outbreak of cases of Acute Hepatitis of Unknown Aetiology whose cause is not yet known and infects children. Based on cases that have occurred, one of the main causes of this ettpktraordinary event is PHBS (Clean and Healthy Lifestyle) and poor sanitation. Therefore, this community service activity is needed as a preventive effort. Education is one of the solutions that can be applied, through knowledge and awareness of a healthy lifestyle is very important to be instilled from an early age. Methods: The methods used in this activity are question and answer lectures and role plays with poster media. Results: The existence of this counseling activity makes children understand and enthusiastic about implementing PHBS in their daily lives. Conclusion: Seeing the positive impact of community service will certainly be better if similar activities can be carried out periodically and delivery is more varied.Keywords: Children, education, healthy lifestyle, hepatitis A